Purchase Decisions on the Shopee Application with the effects of Promotion, Price, Trust and Consumer Reviews - Buyung Romadhoni; Andi Risfan Rizaldi; Asriani Hasan; Amir Amir; Faidhul Adzim (Cita konsultindo, 2024)
This research aims to analyze the influence of promotions, price, trust and consumer reviews on purchasing decisions. In this research, the research method used is quantitative research methods to test the hypotheses that have been established. The population in this research is consumers who have used Shopee services in Makassar City.The type of non-probability sampling method used is judgmental sampling which places limits on respondents who meet the criteria.So the total sample for this research is 96 Shopee consumers. This research uses multiple linear regression analysis. Based on the results of the analysis, it is concluded that the variables promotion, price, trust and consumer reviews each have a positive and significant effect on purchasing decisions.